2021
DOI: 10.19090/pp.2021.3.277-307
|View full text |Cite
|
Sign up to set email alerts
|

Competitive trait anxiety and general self-esteem of athletes according to the sport type and gender

Abstract: Traditionally, anxiety has been interpreted as a negative emotional state characterized by nervousness, worry, fret, uncertainty and vague fear which could have an adverse effect on sports achievement. On the other hand, sport type and its specific nature and demands, may also be connected with the level of state and trait anxiety. This study aimed to investigate potential differences in the competitive trait anxiety level and general self-esteem according to gender in sports of different contact level. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
0
9
0
2
Order By: Relevance
“…Given the above, some studies have investigated coping in sports, integrating variables of sex and type of sport [15,27,37], sex and competitive levels [13,36], sex, age, and type of sport [22], and sport type and experience [38]. However, no studies were found that have dealt with the relationship between competitive anxiety symptoms and competitive level together with a large number of variables, such as the present study.…”
Section: Introductionmentioning
confidence: 96%
“…Given the above, some studies have investigated coping in sports, integrating variables of sex and type of sport [15,27,37], sex and competitive levels [13,36], sex, age, and type of sport [22], and sport type and experience [38]. However, no studies were found that have dealt with the relationship between competitive anxiety symptoms and competitive level together with a large number of variables, such as the present study.…”
Section: Introductionmentioning
confidence: 96%
“…Another reason for the lack of differences in competitive anxiety dimensions between sports types, may have been from the observable overlap between the dynamics of the sport categories (see Table 1). For example, team sports, which have been linked to lower levels of anxiety (Correia & Rosado, 2019), also were the only category to contain contact sports, which have been linked with higher anxiety levels (Kumar et al, 2017; Sanader et al, 2021). Such overlaps may have interfered with apparent levels of anxiety dimensions present between sports, and presents an issue that future research should consider when investigating the effects of situational factors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that individual sports (e.g., archery) illicit higher anxiety than team sports (Correia & Rosado, 2019), because the responsibility for performance is greater and spectator attention is solely focused on the individual. Contact (e.g., boxing) and collision (e.g., football) sports have also shown illicit higher levels of anxiety, because they represent a higher risk of physical injury (Kumar et al, 2017; Sanader et al, 2021). Having an increased social aspect involved in the sport has also shown to increase competitive anxiety, as sports with more direct and larger crowds illicit greater anxiety (Gillham & Gillham, 2014; Wright, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…U tom kontekstu posmatrano, maskulinost i femininost predstavljaju skup psiholoških osobina koje se stereotipno više pripisuju jednom ili drugom polu u određenom društvu i kulturi, u određenom vremenskom trenutku (Kandido -Jakšić, 1995), što može uključivati i fizički izgled, ponašanje, izbor zanimanja, slobodne aktivnosti, itd. U domenu sporta je pitanje ravnopravnosti pokrenuto relativno skoro, iako brojne studije dosljedno pokazuju da je na svim uzrastima i u svim zemljama broj žena i djevojčica koje se bave sportom daleko manji u odnosu na broj muškaraca (Donelly & Donelly, 2013; Keeler, 2007;Pačesova & Šmela, 2020;Petrović, 2020;Sanader et al, 2021). Nakon mnogo neuspješnih direktiva, akcionih planova, istraživanja i ukazivanja na problem, konačni zaokret u odnosu prema jednakoj mogućnosti učestvovanja, a samim tim i dostupnosti sporta, po maksimi "sport za sve", dogodio se na Olimpijskim igrama u Londonu 2012. godine.…”
Section: Uvodunclassified